(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the effectiveness of small business and private entrepreneurship in the development of the countrys economy on the basis of structural changes, and outlines the goals and main directions of its further development. In addition, scientific proposals and conclusions in this regard are given.